2023
DOI: 10.3390/agriculture13112156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Guar Meal from Pig Compound Feed on Productive Performance, Nitrogen Metabolism, and Greenhouse Gas Emissions

Gabriel Mihaila,
Mihaela Habeanu,
Nicoleta Lefter
et al.

Abstract: Guar (Cyamopsis tetragonoloba) is an annual legume tolerant to drought. Guar meal (GM) is a protein- and carbohydrate-rich co-product generated after the mechanical separation of the endosperm from the germ and hull of guar seed. GM has received considerable interest in animal feed as an alternative to soybean meal (SM). In this study, we aimed to assess the nitrogen (N) balance indicators, performance, carcass traits, and main greenhouse gas (GHG) emissions resulting from enteric fermentation (E-CH4) and manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The authors concluded that WDGSs can be used in the liquid feeding of pigs in a proportion of up to 15% of the DM, without affecting the pig performance, carcass traits, meat quality, proximate composition, or physical-chemical traits of pork. Similar topics were also addressed in the papers of Chiofalo et al [21] and Mihaila et al [22]. Chiofalo et al [21] evaluated the agronomic traits, chemical composition, fatty acid profile, and in vitro fermentation characteristics of twelve varieties of Amaranthus spp.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The authors concluded that WDGSs can be used in the liquid feeding of pigs in a proportion of up to 15% of the DM, without affecting the pig performance, carcass traits, meat quality, proximate composition, or physical-chemical traits of pork. Similar topics were also addressed in the papers of Chiofalo et al [21] and Mihaila et al [22]. Chiofalo et al [21] evaluated the agronomic traits, chemical composition, fatty acid profile, and in vitro fermentation characteristics of twelve varieties of Amaranthus spp.…”
mentioning
confidence: 88%
“…Among the varieties studied, A. hypochondriacus proved to have the best agronomic traits and the seeds had the best nutritional value (high protein and starch content and a good fatty acid profile), being potential ingredients for pig diets. Mihaila et al [22] investigated the possibility of substituting soybean meal in pig feed with guar meal, which is a by-product rich in protein and carbohydrates, obtained after mechanical separation of the endosperm from the germ and coat of guar seeds. The obtained results demonstrated that guar flour can replace 100% soybean meal in a pig finishing diet, without changing animal performance or carcass traits, and can have a positive impact on the main greenhouse gas emissions resulting from enteric fermentation (E-CH 4 ) and manure (M-CH 4 and NO 2 ).…”
mentioning
confidence: 99%